2019
DOI: 10.29333/ejgm/108678
|View full text |Cite
|
Sign up to set email alerts
|

The role of hematological parameters in estimating nosocomial sepsis

Abstract: Background: Sepsis is a systemic inflammatory condition with high mortality rate. It is important to estimate nosocomial sepsis in order to manage the patients earlier. The aim of this study was to investigate the role of hematological parameters in estimating nosocomial sepsis. Material and Methods: A retrospective examination was conducted on 121 nosocomial sepsis patients between 01 January 2014 and 30 June 2017. Neutrophil to lymphocyte ratio (NLR) and C-reactive protein (CRP) of the patients at the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
1
0
1
Order By: Relevance
“…The results are parallel with the study done by Loonen et al, who did not find any significant association [26]. In contrast, studies done by Naess et al and Gozdas et al found a significant association between NLR and blood culture positivity [27][28]. The differences observed could be attributed to variation in methodology, sample size, or study population.…”
Section: Discussionsupporting
confidence: 85%
“…The results are parallel with the study done by Loonen et al, who did not find any significant association [26]. In contrast, studies done by Naess et al and Gozdas et al found a significant association between NLR and blood culture positivity [27][28]. The differences observed could be attributed to variation in methodology, sample size, or study population.…”
Section: Discussionsupporting
confidence: 85%
“… 9 Hematological parameters are straightforward variables that may be derived from a patient’s hemogram. 10 The ability to count the various subsets of leukocytes in a patient’s peripheral blood is a helpful tool for detecting a variety of disorders and diseases. Neutrophils play a critical part in the immune response during infection by producing cytokines that attract macrophages and phagocytizing cellular debris.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil ini serupa dengan penelitian yang dilakukan oleh di turki pada subjek dewasa dengan sepsis menunjukkan korelasi yang bermakna antara NLCR dan CRP. 20 Penelitian pada pasien sepsis neonatus di Bandung juga melaporkan adanya korelasi positif antara NLCR dan CRP. 21 Skor PELOD-2 adalah sistem penilaian yang sering digunakan untuk menggambarkan disfungsi organ multipel.…”
Section: Pembahasanunclassified